Analysis of Service Quality on Customer Satisfaction in the Micro KUR Loan Program at Pegadaian UPC Delitua Office - Tirsah, Fadhila; Sari Lubis, Kartika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to examine the impact of service quality on customer satisfaction in the Micro KUR loan program at Pegadaian UPC Delitua Office with a qualitative approach. Through in-depth interviews with 20 customers who have taken advantage of the Micro KUR Loan program at the office, this study identified aspects of service quality that affect customer satisfaction. The results of the analysis show that service quality has an important role in influencing customer satisfaction with the Micro KUR Loan program at Pegadaian UPC Delitua Office. Staff responsiveness, clarity of information, ease of process, and customer trust in Pegadaian were identified as the main factors affecting customer satisfaction. This research emphasizes the importance of improving service quality by companies to ensure a higher level of customer satisfaction in using the Micro KUR Loan program. In addition, emotional factors such as warmth and familiarity in interactions between customers and employees also have a significant contribution to customer satisfaction.